Differences and their contexts between teaching and nonteaching hospitals in Iran with other countries: A concurrent mixed-methods study - Niusha Shahidi Sadeghi; Mohammadreza Maleki; Hassan Abolghasem Gorji; Soudabeh Vatankhah; Bahram Mohaghegh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In terms of missions, hospitals are divided into teaching and nonteaching. In addition, differences in health-care systems in countries will lead to differences in hospitals' operation. Iran, as a specific health-care system, is different from other countries. Hence, the present study investigated differences between teaching and nonteaching hospitals and their differences in Iran and the world. MATERIALS AND METHODS: A concurrent mixed-methods study was conducted in two stages. The first stage was a narrative review of studies (2000-2020). Using narrative inquiry and reflective analysis, the content was analyzed and the categories were extracted. The second stage was a qualitative study conducted using semi-structured interviews with forty Iranian hospital managers and policymakers through a purposive sampling in 2020. Content analysis was made using deductive approach, and MAXQDA 12 was used for data analysis. RESULTS: According to the first stage, categories were extracted as follows: service quality, type of cases, patient satisfaction, efficiency, performance indicators, patient safety, personnel, use of drugs, access to services, technologies, justice in the type of services received, using guidelines, processes, and number of services. In the second stage, 8 main categories, 17 categories, and 45 subcategories were extracted. The extracted main categories were as follows: mission and target, management and behavioral organizations, supply chain and chain of results, human resources, costs and budget, policy demands, clients' satisfaction and patients' right, and integration of medical education. CONCLUSION: Unlike other countries, in Iran, the combination of missions and the complete dependence of teaching hospitals on the government has caused differences. Reducing the treatment mission of teaching hospitals; differences in the budget and development of its indicators; lower tariffs for teaching hospitals; developing a cost-income management model and supply chain; preventing uncertainty other than medical students except medicine; considering the clients' right to choose hospital; and organizing research missions in hospitals were the solutions for decrease differences.